A tale of two MOCs: An adventure fable outlining the constant danger of not following proper process safety protocol. Issue 3 (8th July 2022) - Nelson, Pamela; Ruth, Lisa
Abstract: One of the process safety management (PSM) concepts that so many have struggled with is management of change. It seems so simple on the surface, but it has resulted in serious incidents. Using a story format, two incidents are recited to illustrate what went wrong with management of change (MOC), and how the incidents could have been avoided. A fairy tale story based on the incidents was created to illustrate the importance of MOC. The fairy tale uses familiar character types and forms to illustrate: why the change was not recognized; hazards of uncontrolled changes; and the importance of MOC in the prevention of process safety incidents. The fairy tale story communicates lessons learned from two incidents that resulted from MOC failures.